Analysis of Difference in Microbial Community and Physicochemical Indices Between Surface and Central Parts of Chinese Special-Flavor Baijiu Daqu - Chen, Yanru; Li, Kaimin; Liu, Ting; Li, Ruyi; Fu, Guiming; Wan, Yin; Zheng, Fuping (Frontiers in Microbiology, 2021)
Special-flavor Baijiu is a unique Baijiu in Jiangxi Province, China, whose uniqueness mainly depends on the unique production process of special-flavor Baijiu Daqu. However, the microbial structure and physicochemical indices of different parts of the special-flavor Baijiu Daqu are still unknown. This greatly reduces the actual value of Daqu in the production of special-flavor Baijiu. Therefore, culture-dependent and Illumina MiSeq sequencing methods were used to analyze the microbial structure of special-flavor Baijiu Daqu. The results indicated that there was a complicated microbial diversity in Chinese special-flavor Baijiu Daqu. The predominant bacterial communities were Bacillales, Lactobacillales, and Rhodospirillales, while Saccharomycetales and Eurotiales were the predominant fungal communities. Significant differences in microbial community and distribution were shown between the surface and central parts of Daqu. Acetobacter and Pichia genera were the predominant microorganisms in the surface part of Daqu, whereas Aspergillus, Kroppenstedtia, Oceanobacillus, and Bacillus genera were the predominant microorganisms in the central part of Daqu. Meantime, the different microbial distributions between the surface and central parts of Daqu caused the significant differences in the physicochemical indices. These results can provide an important theoretical basis for improving the brewing process and the quality of special-flavor Baijiu.